2011
DOI: 10.1002/dev.20609
|View full text |Cite
|
Sign up to set email alerts
|

Persistent sensitization of depressive‐like behavior and thermogenic response during maternal separation in pre‐ and post‐weaning guinea pigs

Abstract: Early attachment disruption is thought to promote later onset of depressive illness through a process involving sensitization. Maternal separation in guinea pig pups produces depressive-like behavior and core body temperature fluctuations that appear to be mediated by proinflammatory activity. In pups near the age of weaning (~20 days of age), these responses are increased during repeated separations occurring over several days. Here, enhanced depressive-like behavior and core body temperature responses were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 161 publications
(172 reference statements)
4
26
0
Order By: Relevance
“…2). These increases are not associated with increases in locomotor activity, and neither the behavioral nor the core temperature change can be accounted for by the increasing age of the animals (Schneider et al, 2012; Yusko et al, 2012). The sensitization of the fever response implies a sensitization of inflammatory mechanisms, though this remains to be directly tested.…”
Section: Modeling Effects Of Maternal Separation On the Development Omentioning
confidence: 93%
See 2 more Smart Citations
“…2). These increases are not associated with increases in locomotor activity, and neither the behavioral nor the core temperature change can be accounted for by the increasing age of the animals (Schneider et al, 2012; Yusko et al, 2012). The sensitization of the fever response implies a sensitization of inflammatory mechanisms, though this remains to be directly tested.…”
Section: Modeling Effects Of Maternal Separation On the Development Omentioning
confidence: 93%
“…Even a single 3-hr separation increases the level of passive, but not active, behaviors observed during separation the following day (Schneider et al, 2012). If 3-week-old pups are then separated a third time 4 or 10 days after the first separation, the same heightened level of passive behavior is observed (Hennessy, Paik, Caraway, Schiml, & Deak, 2011; Schneider et al, 2012; Yusko, Hawk, Schiml, Deak, & Hennessy, 2012; Fig. 2).…”
Section: Modeling Effects Of Maternal Separation On the Development Omentioning
confidence: 99%
See 1 more Smart Citation
“…Attachment disruptions can lead to severe psychological and social impairments in both mother and offspring. For instance, mother guinea pigs demonstrate a passive, depressive-type response when separated from their pups across a wide range of infant ages (Schneider, Schiml, Deak, & Hennessy, 2012). As discussed above in the section on social buffering, social support from conspecifics also appears to be important across many species for dealing with difficult circumstances.…”
Section: Social Complexitymentioning
confidence: 99%
“…Subsequent work revealed that the sensitization would persist for more than just 24 hr. For instance, Schneider et al [41] found that pups separated on two consecutive days, and then again 10 days after the first, exhibited more of the passive depressive-like behavior during both of the later separations, as well as a larger and more-rapid fever response, particularly during the last separation.…”
Section: Introductionmentioning
confidence: 99%